FEATURES OF EDUCATIONAL AND METHODICAL WORK AT PIVOTAL TECHNICAL UNIVERSITY - Olga A. Sotnikova; Vladislav V. Sushkov (Высшее образование в России)
The features of educational and methodical work at technical university are considered. These features allow to fulfill requirements of the regional enterprises for training personnel adapted to regional production specifics. The requirements of a definite enterprise take form of an "adapted professional standard" according to which the pivotal university designs educational programs using educational adaptable modules. university. It means including of educational adaptable modules into educational process. Their efficiency in conditions of a pivotal technical college is proved.